2011
DOI: 10.1111/j.1600-051x.2011.01727.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of hospitalization on oral health: a systematic review

Abstract: Hospitalization is associated with a deterioration in oral health, particularly in intubated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
116
0
28

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(153 citation statements)
references
References 36 publications
3
116
0
28
Order By: Relevance
“…This change of behavior can contribute to deterioration of oral health status after only a short period of hospitalization. Moreover, the systematic reviews conducted by Sjögren 7 and Terezakis et al 9 , both using longitudinal, observational studies in ICUs, suggested deterioration of oral health after hospital admission, with an accumulation of dental biofilm due to a lack of oral hygiene and gingivitis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This change of behavior can contribute to deterioration of oral health status after only a short period of hospitalization. Moreover, the systematic reviews conducted by Sjögren 7 and Terezakis et al 9 , both using longitudinal, observational studies in ICUs, suggested deterioration of oral health after hospital admission, with an accumulation of dental biofilm due to a lack of oral hygiene and gingivitis.…”
Section: Discussionmentioning
confidence: 99%
“…the patients' periodontal health status deteriorated within five to 10 days. The onset of the initial signs of gingivitis (swelling, redness and bleeding gingiva) and the formation of calculus in these patients is related to the accumulation of bacterial biofilm and inadequate oral hygiene over the course of the stay in hospital 6,[8][9] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The recent interest in the importance of good oral hygiene in relation to VAP, and the focus of attention on hospital acquired infections highlights the importance of clear recommendations both regarding appropriate oral care for hospitalised patents of any age, particularly in view of recent systematic review highlighting the negative impact of hospitalisation on oral health, 3 and the storage of toothbrushes in hospital environments. While storage issues for toothbrushes of healthy adults in the community may not be a particular concern, perhaps consideration should be given to the needs of the frailer members of the community.…”
mentioning
confidence: 99%